The effect of CPT1B gene on lipid metabolism and its polymorphism analysis in Chinese Simmental cattle. Issue 7 (12th December 2022) - He, Wei; Gao, Ming; Yang, Runjun; Zhao, Zhihui; Mi, Jiaqi; Sun, Hao; Xiao, Hang; Fang, Xibi
Abstract: Carnitine palmitoyltransferase 1B (CPT1B) is a candidate gene that regulates livestock animal lipid metabolism and encodes the rate-limiting enzyme in fatty acid β-oxidation. To explore the effect of this gene on lipid metabolism in cattle, this study examined CPT1B gene polymorphism in Chinese Simmental cattle and the effect of CPT1B on lipid metabolism. The results showed that the triglyceride content increased significantly with increasing CPT1B gene expression in bovine fetal fibroblasts (BFFs) ( p < 0.05), while CPT1B knockout led to decreased CPT1B expression and a downward trend in triglyceride levels. Correlation analysis showed a significant association between the g.119896238 G > C locus and Chinese Simmental cattle backfat thickness ( p < 0.05). Backfat thickness was significantly greater in individuals with the GC genotype (0.93 ± 0.67 cm) than in those with the CC genotype (0.84 ± 0.60 cm). The g.119889302 T > C locus was significantly correlated with arachidonic acid content in Chinese Simmental cattle ( p < 0.05). The arachidonic acid content in the longissimus muscle was significantly higher in CC genotype beef cattle (0.054 g/100 g) than in those with the other two genotypes (0.046 g/100 g, 0.049 g/100 g). These molecular markers can be effectively used for marker-assisted selection in cattle breeding.